EFEKTIFITAS PENGGUNAAN MEDIA VIDEO UNTUK MENINGKATKAN KEMAMPUAN MENGENAL BAHAYA HIV/AIDS BAGI REMAJA TUNARUNGU - Gita Febriana (Universitas Negeri Padang, 2014)
Abstract: This study began with the discovery of the Deaf children in the school of special need education at SLB Ganting Bukittinggi who do not understand about the dangers of HIV / AIDS, HIV Understanding, Understanding AIDS, mode of transmission and Prevention, thus giving researchers an alternative Video to enhance the ability to know the dangers of HIV / AIDS for Deaf teenagers. This study uses the Quasi-experimental research subjects Deaf teenagers in SLB Ganting Bukittinggi of five peoples. The data obtained were analyzed using the U Mann Whitney test. The results of this study indicate that Media Video effectively to improve the ability to know the dangers of HIV / AIDS for Deaf adolescents.